2021
DOI: 10.3390/metabo11070465
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Prunus Responses to PPV Infection: A Way toward the Use of Metabolomics Approach for the Diagnostic of Sharka Disease

Abstract: Sharka disease, caused by Plum pox virus (PPV), induces several changes in Prunus. In leaf tissues, the infection may cause oxidative stress and disrupt the photosynthetic process. Moreover, several defense responses can be activated after PPV infection and have been detected at the phytohormonal, transcriptomic, proteomic, and even translatome levels. As proposed in this review, some responses may be systemic and earlier to the onset of symptoms. Nevertheless, these changes are highly dependent among species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Therefore, growers should have simple and feasible technological monitoring mechanisms to detect the virus in their orchards, especially to detect asymptomatic trees, which are a constant reservoir of the disease. From an agronomic point of view, the use of molecular tools to provide an early diagnostic of the disease in the orchard should be implemented routinely [46,47]. Another diagnostic tool that needs to be studied further is the use of drones to detect symptomatic trees, as these technologies are becoming widely used and have already been useful for other sweet cherry diseases [48].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, growers should have simple and feasible technological monitoring mechanisms to detect the virus in their orchards, especially to detect asymptomatic trees, which are a constant reservoir of the disease. From an agronomic point of view, the use of molecular tools to provide an early diagnostic of the disease in the orchard should be implemented routinely [46,47]. Another diagnostic tool that needs to be studied further is the use of drones to detect symptomatic trees, as these technologies are becoming widely used and have already been useful for other sweet cherry diseases [48].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the large number of diagnostic and molecular characterization studies of plant viruses, fewer investigations have been carried out on the effects of these pathogens on plant physiology and metabolism. However, previous studies have shown that PPV infection produced ultrastructure alterations in Prunus cells, affecting the thylakoids, plastoglobolus, granal, and starch content and indicating that the chloroplast is the most affected cell organelle [ 13 , 22 , 23 , 35 ]. These changes were associated with severe detrimental effects of PPV on photosynthesis and carbohydrate metabolism, affecting photosystem II (PSII), directly or indirectly, by decreasing the amount of rubisco, oxygen-evolving enhancer, and PSII stability factors [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The harmful PPV effects were due to oxidative stress manifested as lipid peroxidation, protein oxidation, electrolyte leakage, the accumulation of hydrogen peroxide, and an imbalance in the antioxidant systems [ 35 , 37 , 38 ]. However, it should be noted that some conflicting results on the physiological alterations and damage to Prunus caused by PPV infection have been reported, likely due to a combination of variables, including metabolic differences among the plant species studied and differences in the process of infection, the level of PPV infection, the time of sampling, and the conditions under which the plants were grown [ 23 , 39 ]. Importantly, all previous investigations were carried out under controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations